The influence of outdoor training on college students’ professional competitiveness: The mediating role of self-efficacy - Wang, Qian; Dai, Yongguan (International Journal of Innovative Research and Scientific Studies, 2024)
To explore the relationship and mechanisms of outdoor training, self-efficacy, and professional competitiveness. A questionnaire survey was conducted among 120 college students who received outdoor expansion training for eight days and seven nights in Panlong Grand View Garden of Xiangtan City through the self-efficacy and professional competitive strength scales. The relationship between outdoor development training, self-efficacy, and professional competitiveness is statistically significant (r = 0.736, 0.821, 0.873, P < 0.01). Self-efficacy mediates outdoor training and professional competitiveness, with a mediation effect value of (0.339-0.537). Outdoor development training can directly affect professional competitiveness through self-efficacy. This study only takes the students of Hunan University of Science and Technology as the research object, and the representativeness of the student group needs to be improved. The questionnaire survey results are biased. The findings emphasize the value of outdoor development training. It is proven that outdoor development training not only has a direct impact on professional competitiveness but also has an indirect impact on professional competitiveness through self-efficacy. This study not only verifies the relationship between outdoor development training and professional competitiveness but also reveals the inner psychological mechanism of the influence of outdoor development training on professional competitiveness. Therefore, the results of this study can provide a theoretical basis for promoting college students’ professional competitiveness.